Determinants of neonatal near-miss among neonates delivered in public hospitals of Ilu Abba Bor Zone, Southwest Ethiopia: An unmatched case–control study during the COVID-19 pandemic - Debele, Gebiso Roba; Siraj, Sabit Zenu; Tsegaye, Dereje; Temesgen, Ermiyas (Frontiers in Public Health, 2022)
Background The neonatal period is the time with the highest risk of neonatal and infant mortality. The COVID-19 pandemic diverted resources from routine maternal health services, which raises the possibility of neonatal near misses (NNMs). To implement prompt treatments that could improve the standard of infant care and lower neonatal mortality, it has been theorized that pinpointing the determinants of NNM during this outbreak is crucial. In light of this, the current study identified the determinants of NNM in neonates delivered in public hospitals of Ilu Abba Bor Zone, South West Ethiopia. Methods An institution-based unmatched case–control study was conducted among randomly selected 303 (101 cases and 202 controls) neonates admitted to Mettu Karl Comprehensive Specialized Hospital (MKCSH) and Darimu Primary Hospital (DPH) from 1 November to 28 December 2020. Data were collected using interviewer-administered structured questionnaire and checklist. The collected data were coded and entered into Epi-Data version 4.6 and then exported to SPSS version 20 for analysis. Adjusted odds ratios (AOR) along with a 95% confidence interval was used to assess the strength of the association, and a p-value < 0.05 was considered to declare the statistical significance in the multivariable logistic regression analysis. Result A total of 303 (101 cases and 202 controls) neonates admitted to MKCSH and DPH were included in the study making a 97.4% response rate. In the multivariable logistic regression analysis, no formal maternal education [AOR = 3.534, 95% CI: (1.194–10.455)], Breech presentation during birth [AOR = 3.088, 95% CI: (1.029–9.268)], < 4 antenatal care (ANC) visits [AOR = 1.920, 95% CI: (1.065–3.461], cesarean section delivery [AOR = 4.347, 95% CI: (1.718–10.996)], antepartum hemorrhage (APH) [AOR = 3.37, 95% CI: (1.23–9.24)], and hypertensive disorders of pregnancy (HDP) [AOR = 4.05, 95% CI: (2.36–11.05)] were independent determinants of NNM. Conclusion The study's result revealed that factors such as education level, birth presentation, ANC visit, mode of delivery, APH, and HDP continued to be important determinants of the NNM in Ethiopia during this pandemic. Therefore, much work is needed to improve neonatal health by providing adequate ANC services and other identified potential determinant factors that predispose the newborn to life-threatening (near-miss) conditions especially during this pandemic.